Propuesta para la implementación de un sistema de seguridad y salud ocupacional en la Facultad de Ciencias de la Ingeniería período 2014 - Huacón Bustamante, Omar Darwin (2015)
Thesis on the implementation of a system of Industrial Safety for the faculty of engineering sciences UTEQ, this work is focused on establishing policies and procedures for the control and supervision of industrial safety. This plan involves performing procedures that lead to the prevention of accidents, labor and sinister through a system of occupational safety and health conditions, for this is very important situational diagnosis of the FCI based on three on three pillars of management such as: administrative, technical and human talent management, considering the functioning of the system considered occupational health and safety so essential teamwork to successfully meet the system performance, so it is of great importance to identify their estimates and proposals to prevent them and to be continuously updated according to the steps implemented through a technical and objective assessment of risk and through changes that may occur on the same machinery as prevention and protective equipment. So that both workers and the company (employers) have as to the development of a system of occupational safety and health at work required by the ministry of labor relations and becomes an indispensable tool for prevention. The Productive Safety, look within its main objectives, comply fully with its mission, so it is essential to implement security systems to ensure compliance